2019
DOI: 10.1038/s41408-019-0186-8
|View full text |Cite
|
Sign up to set email alerts
|

Elevated IgM and abnormal free light chain ratio are increased in relatives from high-risk chronic lymphocytic leukemia pedigrees

Abstract: Abnormal serum immunoglobulin (Ig) free light chains (FLC) are established biomarkers of early disease in multiple B-cell lymphoid malignancies, including chronic lymphocytic leukemia (CLL). Heavy chains have also been shown to be biomarkers in plasma cell disorders. An unanswered question is whether these Ig biomarkers are heritable, i.e., influenced by germline factors. CLL is heritable but highly heterogeneous. Heritable biomarkers could elucidate steps of disease pathogenesis that are affected by germline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
1
4
1
Order By: Relevance
“…These results are in line with previous investigations suggesting a key role of self or foreign antigens in CLL development [2,20,34−36]. In this regard, the presence of immune stimulation was described several years before CLL diagnosis [37], and increased susceptibility to clonal expansions was associated with the development of the disease [38].…”
Section: Discussionsupporting
confidence: 91%
“…These results are in line with previous investigations suggesting a key role of self or foreign antigens in CLL development [2,20,34−36]. In this regard, the presence of immune stimulation was described several years before CLL diagnosis [37], and increased susceptibility to clonal expansions was associated with the development of the disease [38].…”
Section: Discussionsupporting
confidence: 91%
“…Cases and family members wishing to be part of the study were subsequently enrolled by the study team, including informed consent, questionnaires and biospecimens. Individuals in 23 high-risk CLL pedigrees were enrolled as previously described [ 16 ] . Only one six-generation pedigree with 24 CLL cases contained sufficient meioses (m ≥ 15) between sampled CLL cases for SGS analysis [ 17 ] .…”
Section: Methodsmentioning
confidence: 99%
“…A detailed explanation of the SGS method, including optimization over subsets and determination of the genome-wide significance threshold has been described elsewhere [15] . Briefly, a segment is defined as the stretch of consecutive SNPs shared IBS by a subset of cases.…”
Section: Shared Genomic Segment Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies were found looking into the association between IgM levels and the risk of cancer. One study reported an increased risk of chronic lymphocytic leukaemia in patients with increased levels of IgM [ 13 ]. No associations were found with other cancer types (i.e.…”
Section: Immunoglobulin M G a And Ementioning
confidence: 99%